Healthcare workers' attitudes to how hand hygiene performance is currently monitored and assessed. Issue 4 (August 2020) - Cawthorne, K-R.; Cooke, R.P.D.
Summary: Engagement of healthcare workers (HCWs) is critical to maintaining high levels of hand hygiene (HH). However, attitudes of HCWs to how compliance is monitored has been poorly described. This study explored the HCW perspective on direct observation (DO) as a gold standard for HH monitoring. It also sought their opinions on innovative technology. A survey was emailed to all staff in two NHS trusts: 1120 responses were analysed. Nursing staff and doctors accounted for the largest quantity of responses; 58% of HCWs did not strongly endorse DO assessment of HH compliance. Staff were open to considering alternative innovative technologies.